The political culture of the Chilean Socialist Party and its influence on the nomination of Michelle Bachelet as presidential candidate in 2005 - Urbina-Montana, Maria-Loreto (2014)
This study develops a conceptualisation of the political cultures of the Chilean Socialist Party (PSCh) in order to understand and develop an explanation of the nomination of Michelle Bachelet as presidential candidate in 2005 which avoids the oversimplifications of existing approaches. At the theoretical level, political culture is defined from the collective action perspective conceptualising it as a framework for action (Elkin, 1993: 123). This political culture is formed by patterns for political participation which drive internal power relations between members and leaders. The formation of these patterns is influenced by their social context which is mediated by groups of members and leaders in relation to their histories, experiences of critical historical junctures and ideological heritages. The conceptualisation developed thus links structure and agency in a way that enables a nuanced analysis of inter-party power relationships and agency. This fosters a deeper explanation of Bachelet’s nomination and enables evaluation of its meaning for the party as an institution. It also help us to understand internal dynamics and contradictions than could be found in her nomination.